INTRUDUKSI TEKNOLOGI PENGOLAHAN JAGUNG BAGI KELOMPOK WANITA TANI JAGUNG DESA NUNKURUS KECAMATAN KUPANG TIMUR KABUPATEN KUPANG - Marten L. Lano; Jemmy J.S. Dethan; Yuni Kemala Dewi; Ongky G. Toy (Bajang Institute, 2022)
The Women Farmers Group (KWT) Mardika and Tirosa are a farmer group in Uel Hamlet, Nunkurus Village. Nunkurus Village is located in the East Kupang District, Kupang Regency, located ± 37 km east of Kupang City, has 4 hamlets, 10 RW and RT 20. The population of Nunkurus consists of 755 households (700 farmer households and 55 non-farmer families), with a total population of 3,293 consisting of 1,696 men and 1,595 women. Uel is a hamlet in Nunkurus, where this hamlet has 3 RW and 6 RT, with a total of 145 KK Farmers, the area of ​​dry land in Uel is 670 Ha, of which only 200 ha have been processed, the rest are mixed forest, shrubs and sleeping area. The problem faced by KWT partners Mardika and Tirosa in Uel Hamlet, Nunkurus Village, is how to increase the selling value of corn products which are usually sold in dry shelled form, by processing them to increase the selling value. How to design and build a grinding machine as well as a filter with a certain size and how to maintain good quality of ground corn products. This activity aims to change the product from shelled corn into corn flour and corn rice so that it has a higher selling value. From the results of the application of technology to group partners, namely KWT Mardika and KWT Tirosa, there was an increase in income with the application of the technology provided by 20% of the original income, the technology provided adapted to the business carried out by partners, and produced milled corn products with a size of 100 mesh. , 25 mesh and 6 mesh. The product forms are corn flour, fine grain corn rice and coarse grain corn rice.